Exploring students’ ‘epistemic becoming’ on a residence-based education support programme during the COVID-19 PANDEMIC at Stellenbosch University - Petersen, Joy (Stellenbosch : Stellenbosch University, 2026)
Thesis (DPhil)--Stellenbosch University, 2025.